Parpadanan: Model Toleransi Beragama di Desa Simanosor (2005-2015) - Sianturi, Alvan Lamson; Erniwati, Erniwati (Jurnal Kronologi, 2025)
(Abstract) Simanosor Village is a village that has diversity in terms of religion, ethnicity, customs and culture but lives in tolerance without any conflict. The community lives with tolerance which is supported by the Parpadanan Agreement. The purpose of this writing is to see how diversity of religious relations is formed and to find out how community leaders build religious tolerance in Simanosor Village. This research method uses the historical method with stages of writing history, including; Heuristics (Data Collection), Source Criticism, Interpretation (interpretation) and Historiograph (historical writing). From the research results, it was found that religious tolerance is created by cooperation between communities led by religious figures and traditional heads of each tribe as well as the local government Keywords: Parpadanan, Telerance, Harmonization, Religuious Communities Abstrak Desa Simanosor merupakan desa yang memiliki keberagaman dari segi agama suku adat dan budaya namun hidup dalam toleransi tanpa adanya konflik. Masyarakat hidup dengan toleransi yang ditopang oleh Perjanjian Ikatan Parpadanan. Adapun tujuan penulisan ini untuk melihat bagaimana terbentuknya keberagaman hubungan umat beragama dan mengetahui bagaimana tokoh masyarakat membangun toleransi umat beragama di Desa Simanosor. Metode penelitian ini menggunakan metode Sejarah dengan tahap-tahap penulisan Sejarah, diantaranya; Heuristik (Pengumpulan Data), Kritik Sumber, Interprestasi (penafsiran) dan Historiograf (penulisan sejarah). Dari hasil penelitian yang ditemukan toleransi umat beragama tercipta dari kerja sama antar umat yang dipimpin oleh tokoh-tokoh agama dan kepala adat masing-masing suku serta pemerintahan setempat. Kata Kunci: Parpadanan, Toleransi , Hrmonisasi, Umat Beragama